Концепція стратифікації в умовах трансформації українського суспільства - Гончарова, С. Ю.; Семенченко, А. В. (НТУ "ХПІ", 2014)
У статті розглянуті підходи зарубіжних вчених до визначення моделей стратифікації суспільства, об’єднані всі елементи, що стосуються стратифікації суспільства у єдину загальну схему, що дає можливість узагальнити існуючі теоретичні розробки стосовно: типів соціальної стратифікації, видів стратифікаційних структур, системи, критеріїв та підходів до соціальної стратифікації. Отже, необхідно вивчати концепцію стратифікації, оскільки в майбутньому проблема стратифікації гратиме важливу роль в розвитку України.

The article considers the approaches of foreign scientists to the definition of models of the stratification’s society, combined all the elements concerning the stratification’s society into a single General scheme that allows to generalize the existing theoretical development: types of social stratification, species stratified structures, the systems, criteria and approaches to the social stratification. Further development of the stratification processes in the Ukrainian society will undoubtedly affect the nature of the transformation of social structure and largely depend on the speed of the processes of economic reform, socio-cultural peculiarities of post-Soviet countries and their specificity. Therefore, it is necessary to further explore the concept of stratification, because in the future the problem of stratification will play an important role in the development of Ukraine.
The concept of stratification in the conditions of Ukrainian’s transformation of society
Keywords: стратифікація суспільства; концепція стратифікації; сучасні тенденції; соціальна стратифікація; stratification; concept; transformation; society; system; modern trends